Comparative Study of Intralesional Dexamethasone Plus Hyaluronidase & Oral Colchicine in Patients with Oral Submucous Fibrosis - Neupane, Ganesh Prasad; Rai, Maya; Rathore, R. S.; Bhargava, V. K.; Mahat, A. K.; Dhami, D. B. (Journal of Nepalgunj Medical College, 2018)
Introduction: Oral Submucous Fibrosis (OSMF) is a precancerous condition of the oral mucosa. It is characterized by excessive production of collagen leading to inelasticity of the oral mucosa and atrophic changes of the epithelium.Aim and objective: To evaluate the efficacy of oral Colchicine in comparison to intralesional injections of Dexamethasone plus Hyaluronidase in the management of OSMF patients.Materials and Methods: Fourty patients with OSMF were randomly divided equally into two groups. 20 patients in Dexamethasone group received biweekly intralesional injections of Dexamethasone (4mg/ml) plus Hyaluronidase 1500 IU in buccal mucosa for a period of 12 weeks. Other 20 patients in Colchicine group received oral Colchicine 0.5 mg tablets twice daily for 12 weeks. Parameters taken in the study were burning sensation, and mouth opening. Descriptive statistics, paired t test and unpaired t test were used for statistical analysis.Results and Conclusions: The pre- and post-treatment differences were found to be statistically significant for both the groups (p